2021
DOI: 10.3390/jof7050331
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antibacterial, Antifungal, Nematocidal and Growth Promoting Activities of Trichoderma hamatum FB10 and Its Secondary Metabolites

Abstract: Microbial natural biocides have attracted much more attention in recent years in order to avoid the unrestricted use of chemical biocides in the environment. The aim of this study is to analyze the antibacterial and antifungal activities of secondary metabolites and growth promoting, nematicidal, and soil enzyme activity mediated by Trichoderma hamatum FB10. The bactericidal and fungicidal activities were performed using cell-free extract. Results revealed that the selected strain exert antibacterial activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 52 publications
0
22
0
Order By: Relevance
“…Changes in the morphology of R. solanacearum cells (the rupturing of cell walls, the disintegration of the cell membrane, and leakage of cell contents) were observed as a result of the action of various secondary compounds from Trichoderma [165]. Moreover, T. hamatum synthesized the bioactive volatile secondary metabolite, 6PAP, which effectively inhibited the growth of Acidovorax avenae, Erutimacarafavora, and Xanthomonas campestris [167]. Sarsaiya et al [168] demonstrated for the first time that the endophytic strain of T. longibrachiatum, isolated from the medicine plant Dendrobium nobile, produced the dendrobine compound responsible for enhancing human immunity, preventing metastatic cancer, and therapeutic effects on Alzheimer's disease.…”
Section: Trichoderma As a Biocontrol Agent Against Other Plant Pathog...mentioning
confidence: 99%
“…Changes in the morphology of R. solanacearum cells (the rupturing of cell walls, the disintegration of the cell membrane, and leakage of cell contents) were observed as a result of the action of various secondary compounds from Trichoderma [165]. Moreover, T. hamatum synthesized the bioactive volatile secondary metabolite, 6PAP, which effectively inhibited the growth of Acidovorax avenae, Erutimacarafavora, and Xanthomonas campestris [167]. Sarsaiya et al [168] demonstrated for the first time that the endophytic strain of T. longibrachiatum, isolated from the medicine plant Dendrobium nobile, produced the dendrobine compound responsible for enhancing human immunity, preventing metastatic cancer, and therapeutic effects on Alzheimer's disease.…”
Section: Trichoderma As a Biocontrol Agent Against Other Plant Pathog...mentioning
confidence: 99%
“…Alkaline proteases could be used as bio-additive compounds in the textile and food industries and to increase cleaning power [36,42,43]. In this review, Li et al [24] and Lindstrom and Belanger [25] found fungal alkaline proteases of pH 9, 10, and 11, respectively, however, there was no assay for the application of these enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…The fungal pathogen, L. theobromae strain L1, was originally isolated from a root of an infected macadamia tree growing in the same region. Both fungal isolates were identified based on their morphology and the nucleotide sequence of ITS rDNA ( Malachová et al, 2020 ; Baazeem et al, 2021 ). Specifically, the partial nucleotide sequences of ITS rDNA of the strain C9 ( Figure 1A ) and the strain L1 ( Figure 1B ) obtained in our study were 100% identical to those of T. hamatum isolate F4 (NCBI Accession: MT341773.1 ) and L. theobromae isolate FH14K03 (NCBI Accession: MK886711.1 ), respectively.…”
Section: Methodsmentioning
confidence: 99%